Service and leadership in the university: duoethnography as transformation. Issue 3 (22nd June 2018) - Fitzpatrick, Esther; Farquhar, Sandy
Abstract : Purpose: The purpose of this paper is to use duoethnography to explore experiences of service as work in the university, an institution increasingly shaped by neoliberal values. The authors trace the shift in emphasis within the university from one of a care-oriented form of service to a highly managerial form of service. The authors first interrogate childhood stories to make sense of the initial response to the role of service in a lecturer position, and then to the increasing organisational demand for leadership within the university. Design/methodology/approach: As two women academics the authors see the work in teacher education as a particular form of service—as "our calling". Findings: This duoethnography reveals different histories in relation to service, but similar ways of thinking about the changing nature of service in the university. With particular regard to women in the academy, it reveals the desire for a more transformative approach, recognising the importance of collegial relationships, and valuing an ethics of care, in order to develop inclusive and transformative service and leadership in the academy. Practical implications: This paper provides clear links to how changes in the university are understood and approached differently by people. Originality/value: This paper argues for the importance of autoethnographic and duoethnographic explorations of the personal stories in the university to better understand wider definitions of service and leadership.